1990
DOI: 10.2307/3869238
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Transport of Plant Potyviral Proteins

Abstract: We have used immunoblotting, immunocytochemical, and gene fusion methods to examine the differential subcellular partitioning of tobacco etch potyvirus proteins that are potentially associated with RNA replication. From the earliest timepoints at which viral proteins could be detected, proteins Nla (49-kilodalton proteinase) and Nlb (58-kilodalton polymerase) were localized primarily in the nucleus, whereas the 71-kilodalton cylindrical inclusion protein was identified in the cytoplasm. The Nla and Nlb coding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
180
0
2

Year Published

1992
1992
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(189 citation statements)
references
References 11 publications
7
180
0
2
Order By: Relevance
“…It has been shown that the TEV 5' non-coding region can function as an enhancer of translation (Carrington & Freed, 1990). This property could be clue to the likely absence of strong secondary structure, as suggested for the enhancing leaders of other plant viruses (Jobling & Gehrke, 1987;Altmann et al, 1990).…”
Section: Genome Expression: Polyprotein Processingmentioning
confidence: 94%
“…It has been shown that the TEV 5' non-coding region can function as an enhancer of translation (Carrington & Freed, 1990). This property could be clue to the likely absence of strong secondary structure, as suggested for the enhancing leaders of other plant viruses (Jobling & Gehrke, 1987;Altmann et al, 1990).…”
Section: Genome Expression: Polyprotein Processingmentioning
confidence: 94%
“…Primers containing XhoI and BamHI sites were designed at the 5Ј and 3Ј ends of RACE products and used to amplify the full-length RTM1 cDNA. The full-length cDNA was transferred to the pRTL2 vector (19), which contains a cauliflower mosaic virus 35S promoter and 35S terminator. The expression cassette was excised and subcloned into pSLJ755I5.…”
Section: Growth Inoculation and ␤-Glucuronidase (Gus) Activity Assamentioning
confidence: 99%
“…The authentic 68 kDa GUS protein is localized to the cytoplasm but is targeted to the nucleus when tagged with a nuclear protein or an NLS (Restrepo et al, 1990). Using this system, we have previously demonstrated in transfected protoplasts from cultured tobacco cells the nuclear localization of PS-IAA4-like (Oeller et a/., 1993;Theologis eta/., 1985), early auxin-inducible polypeptides (Abel eta/., 1994).…”
Section: Nuclear Localization Of Hybrid Gus Proteinsmentioning
confidence: 99%
“…We transfected mesophyll protoplasts with the plant expression vector pRTL2-GUS (Restrepo et a/., 1990) and followed the expression of the GUS reporter gene driven by the CaMV 35s promoter. Neither freshly prepared nor mock-transfected Arabidopsis mesophyll protoplasts contained detectable levels of endogenous GUS activity but supported high levels of GUS expression after transfection with pRTL2-GUS.…”
Section: Transient Expression Of Gus Activitymentioning
confidence: 99%